Adjunctive Nebulized Antibiotics: What Is Their Place in ICU Infections? - Niederman, Michael S. (Frontiers in Medicine, 2019)
Inhaled antibiotics have been used as adjunctive therapy for patients with pneumonia, primarily caused by multidrug resistant (MDR) pathogens . Most studies have been in ventilated patients, although non-ventilated patients have also been included (but not discussed in this review), and most patients have had nosocomial pneumonia. Aerosolized antibiotics are generally added to systemic therapy, and have shown efficacy , primarily as salvage therapy for failing patients and as adjunctive therapy after an MDR gram-negative has been identified. An advantage to aerosolized antibiotics is that they can achieve high intra-pulmonary concentrations that are potentially effective , even for highly resistant pathogens, and because they are generally not well- absorbed systemically, it is possible to avoid some of the toxicities of systemic therapy. When using inhaled antibiotics, it is essential to choose the appropriate agent and the optimal delivery method. Animal and human studies have shown that aerosolized antibiotics reach higher concentrations in the lung than systemic antibiotics, but that areas of dense pneumonia may not receive as much antibiotic as less affected areas of lung. Optimal delivery in ventilated patients depends on device selection , generally with a preference for vibrating mesh nebulizers and with careful attention to where the device is placed in the ventilator circuit and how the delivery is coordinated with the ventilator cycle. Although some studies have shown a benefit for clinical cure, adjunctive therapy has not led to reduced mortality. In some studies, adjunctive aerosol therapy has reduced the duration of systemic antibiotic therapy, thus serving to promote antimicrobial stewardship. Two recent multicenter, randomized, double-blinded , placebo- controlled trials of adjunctive nebulized antibiotics for VAP patients with suspected MDR gram-negative pneumonia were negative for their primary endpoints. This may have been related to trial design and execution and the lessons learned from these studies need to be incorporated in any future trials. Currently, routine use of adjunctive aerosolized therapy cannot be supported by available data, and this therapy is only recommended to assist in the eradication of highly resistant pathogens and to be used as salvage therapy for patients failing systemic therapy.